Aonla based intercropping fetches more under dryland conditions - Singh, A K; Singh, Sanjay; Rao, V V Appa; Mishra, D S; Saroj, P L (Indian Horticulture, 2020)
For sustainable crop production in dryland conditions, growing of intercrop in fruit orchard, farmers can maximize the water use efficiency, maintain soil fertility, reduce the weed growth, minimize the soil erosion, full utilization of intrspaces left in orchard, which ultimately leads to sustainable production and doubling the farm income. Keeping these points in mind, different combinations of cucurbitaceous crops, viz. aonla + bottlegourd, aonla + pumkin, aonla + bitter goud, aonla + cucumber and aonla + sponge gourd were investigated in the NA-7 aonla orchard, sapced at 10 mÃ—10 m, attained the age of 8 years, grown uder rainfed semiarid conditions. Results of study revealed that the aonla based intercopping with cucurbits in kharif is practically feasible and economically viable under rainfed semi-arid ecosystem. Among the different cucurbits tried as an intercrops, net economic return to the tune of f147312.80/ha with the B:C ratio 4.44 was achieved in aonla + bottle gourd followed by aonla + pumpkin combination under purely rainfed conditions of semi-arid ecosystem of western India. In order to obtain more sustainable returns in dryland condition, intercropping not only enhances the productivity and income but also utilizes the unutilized space left in orchards.